Status quo and prospects of the translational research on lung cancer in China - Zhan, Ping; Song, Yong (Translational Lung Cancer Research; Vol 1, No 1 (March 18, 2012): Translational Lung Cancer Research, 2012)
To shed light on the development and prospects of lung cancer translational research in China, a questionnaire survey has been designed and distributed via a domestic medical and life science website-DXY (http://www.dxy.cn/), including the concept of translational medicine, EGFR mutations in lung cancer, EML4-ALK fusion gene, IPASS study, OPTIMAL study, lung cancer GWAS, prospects and recommendations and other contents. DXY is the largest online academic portal for five million Chinese physicians and life science professionals, with average daily page views of 1.8 millions. It was established in 2000, and now has over 2.6 million registered members. DXY features >100 columns to facilitate communication, information sharing and collaboration of medical professionals within practically all sub-specialties of clinical medicine, basic medical research, life sciences, and pharmaceutical sciences.